A Randomised Pilot Study on the Efficacy of Milking Cream and a Homeopathic Complex Topical Cream on Diaper Dermatitis - Janice Pellow; Marlo Swanepoel (AOSIS, 2013)
Diaper dermatitis (DD) is an acute inflammation of the skin in the diaper area and is the most common cutaneous disease among infants and children. Calendula officinalis, Atropa belladonna and Sulphuricum acidum are homeopathic remedies which have been purported to be beneficial in wound healing and conditions affecting the skin, however, to date, no research has been conducted on the use of these remedies for DD. The aim of this seven-day, double-blind, controlled pilot study was to assess the efficacy of milking cream and a homeopathic complex cream as topical treatments for DD. Forty children between the ages of three to 24 months with DD were recruited. The homeopathic complex cream (n = 20) or unmedicated milking cream (n = 20) was applied after every nappy change for seven days. Efficacy on the severity of symptoms and the percentage of area affected was assessed by means of the 4-Point Grading Scale and the Modified Lund and Browder Charts respectively, on days 1, 2, 4 and 7. The results revealed that both groups showed statistically-significant improvements on rash severity and the percentage of area affected between consecutive visits, as well as over the entire research study period. Trends indicated that the treatment group had a faster resolution of symptoms and outperformed the control in certain affected body regions. Preliminary findings suggest that both milking cream and the homeopathic complex cream may be effective alternative treatment options for DD, and further investigation is warranted. Luier dermatitis (LD) is 'n akute inflammasie van die vel in die luier area en is die algemeenste velsiekte onder babas en kleuters. Calendula officinalis, Atropa belladonna en Sulphuricum acidum is beweerde homeopatiese middels wat voordelig is in wondgenesing en ander velkondisies. Tot ophede is daar geen navorsing gedoen op die doeltreffendheid van die bogenoemde middels op LD nie. Die doelwit van die sewe dag, dubbele-blinde, beheerde-loodsstudie was om die doelteffendheid van melksalf en 'n homeopatiese mengsel te evalueer as topikale behandelinge vir LD. Veertig babas tussen die ouderdomme van drie maande tot 24 maande was gewerf om deel te neem aan die studie. Die homeopatiese mengsel room (n = 20) of die melksalf (n = 20) was aangewend met elke luier vervanging vir sewe dae lank. Die doeltreffendheid van die room was beoordeel op dag 1, 2, 4 en 7 aan die erns van die simptome en die persentasie gebied wat geraak was, met behulp van 'n 4-Punt Graderingsskaal en die Gewysigde Lund en Browder Grafiek onderskeidelik. Uitslae het getoon dat die behandelingsgroep en die kontrolegroep albei statistiese, beduidende verbeteringe getoon het op die erns van die uitslag en die persentasie gebied wat geraak is, tussen opeenvolgende besoeke sowel as die hele studie tydperk. Tendense dui daarop dat die behandelingsgroep 'n vinniger oplossing van simptome getoon het en beter gevaar het as die kontrolegroep in sekere geaffekteerde liggaamstreke. Voorlopige bevindinge dui daarop dat beide melksalf en die homeopatiese mengsel room effektiewe, alternatiewe behandelings opsies vir LD is en dat verdere ondersoek geregverdig is.